Golden letters : writing traditions of Indonesia = Surat emas: budaya tulis di Indonesia - Gallop, Annabel Teh; Arps, Ben (British Library, 1991)
Catalog of travelling photographic exhibition of royal Indonesian letters and manuscripts from British collections